(untitled) (Mantichora. Italian Journal of Performance Studies, 2025)
The article proposes to tackle the relation between an object of art and its interlocutor/spectator or artist, individuating in Roland Barthes’ punctum, the core aspect of this more often than not, uneven conversation, within which a ‘thing’ deprived of its own voice, imposes strikingly with the intention of becoming ‘something’. A ‘real thing’ – in its power to open new space-time portals, to even cancel the death and transience, inviting the other part in a dialog to enter the facticity of here and how – when encountered directly and disarmingly, touches the profound chords of the self of its ‘discoverer’. The article, thus, pauses on different meanings of the term ‘thing’, finding, in Tom Stoppard’s, Romeo Castellucci’s and René Magritte’s works, the examples of the encounter with the matter which simultaneously grounds itself and goes beyond itself.